UV-Spectrophotometric Determination of Valacicyclovir and Ceftriaxone Sodium - Gowri Sankar, D.; Sujatha, N.; Anil Kumar, B.; Madhavi Latha, P.V. (Asian Journal of Chemistry, 2010)
A simple and sensitive UV spectrophotometric method has been developed for the determination of valacicyclovir and ceftriaxone sodium in pure and pharmaceutical formulations. These methods exhibit maximum absorption at 254 nm for valacicyclovir and 240 nm for ceftriaxone sodium and both the methods obey Beer's law in the concentration range 5-25 μg/mL. The methods are accurate and precise and are extended to pharmaceutical formulations and there was no interference from common pharmaceutical additives and excepients. The results of analysis have been validated statistically and by recovery studies.